THE EYE — MIRROR OF CARDIOVASCULAR DISORDERS. EVOLUTION OF PERCEPTION ABOUT HYPERTENSIVE RETINOPATHY - V. S. Zadionchenko; T. V. Adasheva; A. M. Shamshinova; M. A. Arakelyan (Рациональная фармакотерапия в кардиологии)
Published data often contain conflicting views on the relationship of retina changes in arterial hypertension (HT) with cardiovascular disorders and target organs lesions. Along with the classification and pathophysiology of hypertensive retinopathy, evidence for its association with the HT course, target organ lesions and prognosis is presented. Functional disorders of the eyes point at the involvement of retina into the pathological process even in HT early stages and are able to reflect the severity of hypertension. This supports a close relationship of HT with eye disease as a target organ. Available data support also possibility to assess changes on the eye fundus in patients with uncomplicated HT, indicating that it was premature decision to exclude eyes from the list of target organs in HT.